Answer:
![\frac{x^3+7x^2+9x-8}{x+2}=x^2+5x-1+\frac{-6}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%2B7x%5E2%2B9x-8%7D%7Bx%2B2%7D%3Dx%5E2%2B5x-1%2B%5Cfrac%7B-6%7D%7Bx%2B2%7D)
So the quotient is
and the remainder is
.
Step-by-step explanation:
We could do this by synthetic division since the denominator is a linear factor in the form
.
Since we are dividing by
, this is our setup for the synthetic division:
-2 | 1 7 9 -8
| -2 -10 2
______________
1 5 -1 -6
So the quotient is
and the remainder is
.
So
.
We can also do long division.
x^2+5x-1
____________________
x+2| x^3+7x^2+9x-8
-(x^3+2x^2)
-------------------
5x^2+9x-8
-( 5x^2+10x)
--------------------
-x-8
-(-x-2)
--------------
-6
So we see here we get the same quotient,
. and the same remainder,
.
Now let's check our result that:
.
So I'm going to rewrite the right hand side as a single fraction:
.
![\frac{x^3+7x^2+9x-8}{x+2}=\frac{(x+2)(x^2+5x-1)-6}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%2B7x%5E2%2B9x-8%7D%7Bx%2B2%7D%3D%5Cfrac%7B%28x%2B2%29%28x%5E2%2B5x-1%29-6%7D%7Bx%2B2%7D)
Now let's focus on multiplying
.
We are going to multiply the first term of the first ( ) to every term in the second ( ).
We are also going to multiply the second term of the first ( ) to every term in the second ( ).
![x(x^2)=x^3](https://tex.z-dn.net/?f=x%28x%5E2%29%3Dx%5E3)
![x(5x)=5x^2](https://tex.z-dn.net/?f=x%285x%29%3D5x%5E2)
![x(-1)=-x](https://tex.z-dn.net/?f=x%28-1%29%3D-x)
![2(x^2)=2x^2](https://tex.z-dn.net/?f=2%28x%5E2%29%3D2x%5E2)
![2(5x)=10x](https://tex.z-dn.net/?f=2%285x%29%3D10x)
![2(-1)=-2](https://tex.z-dn.net/?f=2%28-1%29%3D-2)
---------------------------Combine like terms:
![x^3+(5x^2+2x^2)+(-x+10x)+-2](https://tex.z-dn.net/?f=x%5E3%2B%285x%5E2%2B2x%5E2%29%2B%28-x%2B10x%29%2B-2)
![x^3+7x^2+9x-2](https://tex.z-dn.net/?f=x%5E3%2B7x%5E2%2B9x-2)
So let's go back where we were in our check of
:
![\frac{x^3+7x^2+9x-8}{x+2}=\frac{(x+2)(x^2+5x-1)-6}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%2B7x%5E2%2B9x-8%7D%7Bx%2B2%7D%3D%5Cfrac%7B%28x%2B2%29%28x%5E2%2B5x-1%29-6%7D%7Bx%2B2%7D)
![\frac{x^3+7x^2+9x-8}{x+2}=\frac{x^3+7x^2+9x-2-6}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%2B7x%5E2%2B9x-8%7D%7Bx%2B2%7D%3D%5Cfrac%7Bx%5E3%2B7x%5E2%2B9x-2-6%7D%7Bx%2B2%7D)
![\frac{x^3+7x^2+9x-8}{x+2}=\frac{x^3+7x^2+9x-8}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%2B7x%5E2%2B9x-8%7D%7Bx%2B2%7D%3D%5Cfrac%7Bx%5E3%2B7x%5E2%2B9x-8%7D%7Bx%2B2%7D)
We have the exact same thing on both sides so we did good.